PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BANK CENTRAL ASIA TBK KCU MATRAMAN - Matheus Alexander Rio; Donny Dharmawan (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This study aims to determine: The effect of work motivation and work discipline on the performance of employees of PT. Bank Central Asia, Tbk KCU Matraman. This research is a causal associative research using a quantitative approach. The subjects of this study were employees at PT. Bank Central Asia, Tbk KCU Matraman as many as 63 employees. Collecting using questionnaires and interviews while data analysis is done using multiple linear regression analysis. The results of the study at a significance level of 5% indicate that: (1) work motivation has a positive and significant effect on the performance of employees of PT. Bank Central Asia, Tbk KCU Matraman, (2) work discipline has a positive and significant effect on the performance of the employees of PT. Bank Central Asia, Tbk kcu Matraman, (3) work motivation and work discipline have a significant effect on the performance of employees of PT. Bank Central Asia, Tbk KCU Matraman.